Infectious Complications after Orthotopic Liver Transplantation - Patel, Gopi; Huprikar, Shirish (Seminars in Respiratory and Critical Care Medicine, 2012)
Advances in surgical technique, critical care, immunosuppression, donor and recipient screening, and prophylactic strategies have contributed to the evolving microbiology and epidemiology of infectious complications after liver transplantation. Although decreased overall, infections continue to be a major contributor to graft loss and patient morbidity. Bacterial and candidal infections are less frequent, but antimicrobial resistance has become more common and can potentially limit successful treatment of health care–acquired and surgical site infections. As the transplant population grows, intensivists and pulmonologists are more likely to evaluate liver transplant recipients with infections. Presentations of opportunistic respiratory infections may be atypical in the setting of immunosuppression. Although novel noninvasive diagnostic tools are available for some pathogens, bronchoscopic evaluation may be increasingly helpful in differentiating between certain respiratory pathogens when empirical therapy is plagued by drug interactions and drug toxicities. Knowledge about common postoperative infections and opportunistic respiratory pathogens such as cytomegalovirus and fungi is essential to improving the global care of the liver transplant recipient.
Keywords: liver transplant; bacterial infection; fungal infection; cytomegalovirus